Reposessing Islam: Affective Identity and Islamic Fundamentalism in Hanif Kureishi - Andreas Athanasiades (Indialogs: Spanish Journal of India Studies, 2015)
The present article argues that the processes which seem to have spawned the contemporary generation of British jihadists started in 1980s Britain, when Thatcherite practices led to the rise of racism and the suppression of dissident voices, a by-product of which was the disassociation of Muslim immigrants from the host society. The result was that the next generation of immigrants was much more prone to religious violence, attracted as it was towards the -supposedly- stable sense of identity offered by Islamic fundamentalism. The issue of identity of British Muslim immigrants is examined by revisiting Hanif Kureishi’s The Black Album (1995), whose narrative representations open up spaces in the British cultural landscape to intentionally include the marginalised and disenfranchised. The hypothesis is that the essentialist choice faced by his characters within the conflictual context generated by the clash of Islamic fundamentalism and sexual liberation is similar to the one diasporic subjects face today. The argument is that the process of thinking about identity in affective terms, based on the theories of the likes of Brian Massumi and Deleuze and Guattari, gestures towards a new way of addressing questions of belonging for diasporic subjects, which can have a profound effect on the perception of issues such as religious fundamentalism and social integration.